Biological Characteristics and Medical Treatment of Breast Cancer in Young Women—A Featured Population: Results from the NORA Study - P. Pronzato; G. Mustacchi; A. De Matteis; F. Di Costanzo; E. Rulli; I. Floriani; M. E. Cazzaniga (International Journal of Breast Cancer)
Background. The present paper described the biological characteristics and clinical behavior of young women in the cohort NORA study Patients and Methods. From 2000–2002, patients (𝑁>3500) were enrolled at 77 Italian hospitals. Women aged ≤50 years (𝑁=1013) were stratified into age groups (≤35, 36–40, 41–45, and 46–50 years). The relationship between age and patient characteristics, cancer presentation, and treatment was analyzed. Results. Younger women more frequently had tumors with ER/PgR-negative(𝜒2=7.07; 𝑃=.008), HER2 amplification (𝜒2=5.76; 𝑃=.01), and high (≥10%) Ki67 labelling index (𝜒2=9.53; 𝑃=.002). Positive nodal status, large tumors, and elevated Ki67 all associated with the choice for chemotherapy followed by endocrine therapy in hormone receptor-positive patients (𝑃<.0001). At univariate analysis, ER-ve status, chemotherapy and age resulted as the only statistically significant variables (HR=2.02, 𝑃=.004, and >40 versus ≤40, 𝑃<.0001, resp.). At multivariate analysis, after adjustment for significant clinical and pathological factors, age remains a significant prognostic variable (HR=0.93, 𝑃=.0021). Conclusion. This cohort study suggests that age per sè is an important prognostic factor. The restricted role of early diagnosis and the aggressive behavior of cancer in this population make necessary the application of targeted medical strategies crucial.